Blow up boundary solutions of some semilinear fractional equations in the unit ball. (July 2016) - Ben Chrouda, Mohamed; Ben Fredj, Mahmoud
Abstract: For γ > 0, we are interested in blow up solutions u ∈ C + ( B ) of the fractional problem in the unit ball B . We distinguish particularly two orders of singularity at the boundary: solutions exploding at the same rate than δ α 2 − 1 ( δ denotes the Euclidean distance) and those higher singular than δ α 2 − 1 . As a consequence, it will be shown that the classical Keller–Osserman condition cannot be readopted in the fractional setting.